Síntese, caracterização e estudo catalítico de complexos miméticos das enzimas Nitrito Redutase e Anidrase Carbônica - Ferreira, Millena Pereira (Universidade Federal de São Carlos, 2022)
Metalloenzymes are efficient biological catalysts that inspire the creation of coordination compounds that mimic their active site. In this work, the synthesized complexes were inspired by two enzymes: Nitrite Reductase containing Copper (Cu-NiRs) and Carbonic Anhydrase. CuNiRs catalyze the nitrite reduction to nitric oxide, whereas the enzyme Carbonic Anhydrase, acts on the hydration of CO2. Both of these enzymes contain the active site with the same binding environment “NNN”. Therefore, three new tridentate ligands were synthesized, which differ among them by the phenyl, n-butyl and n-propanol substituent groups. These ligands gave rise to the three Cu2+ complexes and three Zn2+ complexes mimetic of the Cu-NiRs and carbonic anhydrase enzymes, respectively. All complexes were characterized by microanalysis, FTIR, conductivity and UV-Vis spectroscopy. The copper complexes were also analyzed by EPR, whereas the zinc complexes were studied by NMR spectroscopy. Both classes of complex, Cu2+ and Zn2+, have the tridentate ligands coordinated to the metals forming pentacoordinate structures with two water molecules completing the coordination sphere. The catalytic activities were dependent on the different substituent groups of the ligands. In the catalytic tests with the copper complexes, it was observed that the NO2‾ coordinates in the bidentate form. After the addition of benzoic acid, EPR and UV-Vis spectroscopies indicate that the nitrite changes the coordination mode from κ2-ONO to κ1-NO2. Although all three copper complexes were able to reduce nitrite to NO both chemically and electrocatalytically, the most efficient catalyst was the one containing the n-propanol group in the second coordination sphere. Our analyses reveal that n-propanol is capable of transferring protons in a proton-coupled electron transfer mechanism, aiding the reaction. For the carbonic anhydrase catalysis, all complexes were also able to hydrate CO2, and the complex with the n-propanol substituents showed a faster bicarbonate formation because its OH group helps in the coordinated water deprotonation step. Therefore, the complexes proved to be good enzyme mimetic catalysts.
Synthesis, characterization and catalytic study of mimetic complexes of the enzymes Nitrite Reductase and Carbonic Anhydrase
Keywords: Complexos miméticos; Nitrito redutase; Geração de NO; Anidrase carbônica; Complexos de Cobre; Hidratação do CO2; Mimetic complexes; Nitrite reductase; NO generation; Carbonic anhydrase; Copper complexes; CO2 hydration; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::DETERMINACAO DE ESTRUTURA DE COMPOSTOS INORGANICOS; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::QUIMICA BIO-INORGANICA